Mast cell adhesion to fibronectin. - Dastych, J (1991)
The MCP-5 murine mast cell line, as well as primary bone marrow-derived cultured mast cells (BMCMC), are demonstrated to bind to fibronectin, a ubiquitous adhesion protein of the extracellular matrix. BMCMC required activation by phorbol myristate acetate (PMA) to adhere to fibronectin, whereas MCP-5 displayed spontaneous adherence. The binding of both MCP-5 and BMCMC was dose dependent, with maximal adhesion at a fibronectin concentration of 20 micrograms/ml. The 120,000 molecular weight (MW) proteolytic fragment of fibronectin containing the RGDS cell attachment site was able to substitute for the native fibronectin molecule in promoting mast cell attachment. Mast cell adhesion to fibronectin, in addition, could be inhibited by the RGDS peptide alone. These data suggest that, in addition to the previously described mast cell-laminin interactions, mast cells also adhere to fibronectin, thus providing further insight into their tissue localization and possible roles in processes such as wound healing and fibrosis.